Using Technology for Deaf Students to Learn English as a Foreign Language in Saudi Arabia - Al Zaylai, Abdullah Saud Abubakr (Journal of Educational and Psychological Sciences, 2019)
The study examines the use of technology to assist the Deaf students to learn English as a foreign language in Saudi Arabia. The growth in technology has changed the delivery mode in education, including that of the disabled. The study evaluates the level of technology application in teaching the deaf students and determines the possibility of improving it. The importance of the study is to provide ways in which the deaf students can be motivated to learn English effectively. The study uses qualitative research strategy. In addition, interviews have been used as data collection instruments. The study concludes that the use of technology to teach English to the deaf students in Saudi Arabia improves its effectiveness. The study encourages the application of these technologies in teaching English for the deaf students in Saudi Arabia.